Determination of flow units of Yamama Formation in the West Qurna oil field, Southern Iraq - Handhal, Amna M.; Al-Najm, Fahad M.; Chafeet, Hussein A. (Iraqi Journal of Science, 2018)
The major objective of this paper is to recognize the flow units of Yamama Formation in the west Qurna oil field, south of Iraq. To attain this objective, four wells namely, WQ-23, WQ-148, WQ-60, and WQ-203 are selected and analyzed. The two techniques hat proposed by some scientists to identify flow units are tested and verified. Results are also enhanced using well logs interpretation and the flow areas are proposed through the studying of the behavior of different well logs. Results of applying the two proposed techniques identify six flow reservoir units for the wells WQ-23, WQ-148, WQ-60, and WQ-203, respectively. This study also shows that the flow reservoir properties in the Yamama Formation improved towards the northeast of the West Qurna oil field.